Legal regulation of land use of individuals for agricultural purposes in Belarus - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2022)
The features of the legal regulation of land use of individuals for agricultural purposes, due to the objects and subject composition of these legal relations, are considered, taking into account the provisions of the new edition of the Code of the Republic of Belarus on Land, which comes into force on 1 January 2023. Innovations that affect the land-legal status of individuals as agricultural producers are analysed. Proposals have been formulated to improve the legal support for the agricultural activities of these entities. The necessity to establish the agricultural purpose of their use of land plots in the legislation has been substantiated and, in this regard, to clarify the basis for the termination of rights to a land plot, the Unifed classifcation of the purpose of real estate objects. It is concluded that it is necessary to expand the legislative concept of a land user.